Effect of Zn:S molar ratio in solution on the properties of ZnS thin films and the formation of ZnS nanorods by spray pyrolysis. Issue 2 (31st January 2014) - Dedova, T.; Krunks, M.; Gromyko, I.; Mikli, V.; Sildos, I.; Utt, K.; Unt, T.
<x xml:space="preserve">Abstract</x> The ZnS layers morphology, structure, composition, and optical properties were investigated with respect to the precursors (zinc chloride and thiocarbamide, Zn:S) molar ratio in spray solution (1:1, 1:2, and 1:3) and growth temperatures in the range of 400–600 °C. Scanning electron microscopy (SEM), X‐ray diffraction (XRD), energy dispersive X‐ray analysis (EDX), UV–VIS, and PL spectroscopy were applied to characterize the ZnS layers. Layers obtained at temperatures up to 450 °C are not well crystallized and contain residues originated from undecomposed precursors. ZnS films become crystalline at Ts = 500 °C. Layers grown from 1:1 solution at 550 °C are mixture of ZnS and ZnO phases, whereas at 600 °C layers of ZnO were obtained. Films produced from 1:2 solution at 500–600 °C are of ZnS with a wurtzite structure and Eg of 3.66 eV, but contain traces of ZnO phase when grown at 550 or 600 °C. Appearance of ZnO phase in the films grown from 1:1 and 1:2 solutions is explained by the results of the studies on the formation and decomposition of dichlorobis(thiocarbamide)zinc(II) complex as an intermediate compound formed in the solution of zinc chloride and thiocarbamide. Spraying the solutions with Zn:S = 1:3, which contain more thiocarbamide than required for the complex formation, results in single‐phase ZnS layers with wurtzite structure at growth temperatures up to 600 °C. Moreover, ZnS layers obtained from 1:3 solution at 550 °C and higher are composed of highly c‐axis oriented ZnS nanorod‐like crystals with diameter of ca. 80 nm and length of ca. 300 nm. <inline-graphic xlink:href="ark:/27927/pgg4swd4bv4" content-type="pssa201300215-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />